2012
DOI: 10.4236/aim.2012.23046
|View full text |Cite
|
Sign up to set email alerts
|

Some Characteristics of a Plant Growth Promoting <i>Enterobacter</i> sp. Isolated from the Roots of Maize

Abstract: Some properties of an Enterobacter sp. isolated from the roots of maize are described. Isolation was carried out using the semisolid enrichment culture technique and subsequent plating, both on nitrogen free biotin medium. Morphological, biochemical and phylogenetic characterization using the MicroSeq  16S rDNA technique were employed in identification of isolate, which was revealed to be closest matched at 99.4% with Enterobacter asburiae. The isolate possessed properties of plant growth promoting bacteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Islam et al [18] reported the phosphate solubilization index of the rice isolates varied from 1.2 to 6.7. Many species of rhizobacteria including Bacilli, Pseudomonas and Klebsiella can solubilise insoluble phosphates in the agar assay in vitro [19][20]. Quantitative estimation in NBRIP broth reveals 17.4±1.78µg/ml solubilised P (Table 1).…”
Section: Phosphate Solubilization Activitymentioning
confidence: 99%
“…Islam et al [18] reported the phosphate solubilization index of the rice isolates varied from 1.2 to 6.7. Many species of rhizobacteria including Bacilli, Pseudomonas and Klebsiella can solubilise insoluble phosphates in the agar assay in vitro [19][20]. Quantitative estimation in NBRIP broth reveals 17.4±1.78µg/ml solubilised P (Table 1).…”
Section: Phosphate Solubilization Activitymentioning
confidence: 99%
“…Aspartic, glutamic acid and glycine were the greatest components (425.4, 354.78 and 401.44). Ogbo and Okonkwo (2012) found that the production of ammonia is frequently reported for PGPR, a process most probably resulting from the deamination (ammonification) of amino acids present in the peptone used for this assay. It has been suggested that ammonia may have a role in antagonism against competing flora, particularly the fungi.…”
Section: Qualitative Analysis Of Essential Oilmentioning
confidence: 85%
“…asburiae + half dose of N2 gave high ratio of N2 compared with control in the second cut (0.895%). Ogbo and Okonkwo (2012) reported that the higher concentration of nitrogen in maize seedlings treated with inoculums by Enterobacter sp. compared with those grown without it inoculation.…”
Section: -Chemical Analysismentioning
confidence: 99%
“…This differential medium has the same composition than Nfb medium but, instead of BTB, Congo red dye was used to increase selectivity for identifying the Azospirillum genus . However, some authors used the RC medium for Azospirillum isolation and they found out typical scarlet red colonies which were identify as Pseudomonas , Bacillus , Streptococcus , and Enterobacter genera .…”
Section: Discussionmentioning
confidence: 99%
“…Different letters in superscript indicate significant differences in the average absorbance values between strains for each CS, using the Tukey's test (p 0.05). were identify as Pseudomonas, Bacillus, Streptococcus, and Enterobacter genera [29,31,32,33].…”
Section: Discussionmentioning
confidence: 99%